Association of albumin levels with the risk of intracranial atherosclerosis - Xiaoyu Lin; Fangfang Ke; Maohua Chen (BMC Neurology, 2023)
Abstract Objective Intracranial artery stenosis from atherosclerosis is one of the etiologies of ischemic stroke. There is a correlation between serum albumin level and atherosclerosis. We aimed to investigate whether serum albumin level is related to intracranial atherosclerosis and its significance. Methods A retrospective analysis of 150 individuals who underwent cervical cerebral angiography after admission, including clinical data, imaging data, and laboratory data. Since atherosclerosis cannot be used as a good quantitative indicator, we choose the degree of arterial stenosis to reflect atherosclerosis. SPSS 24 software was used for data analysis, and P < .05 was considered statistically significant. Results Univariate analysis showed that age, diabetes, and serum albumin level were risk factors for intracranial atherosclerosis (P < .05). Multivariate analysis showed that diabetes and serum albumin levels were independent risk factors for intracranial atherosclerosis (P< 0.05). The average serum albumin level in the non-severe group was 39.80 g/L, and the average serum albumin level in the severe group was 37.60 g/L. The area under the ROC curve of serum albumin was 0.667 (95%CI 0.576–0.758, P = .001), the cutoff value was 0.332176, the sensitivity was 75.9%, and the specificity was 57.3%. Conclusion Serum albumin level is an independent risk factor for intracranial atherosclerosis, and provides a new direction for clinical prevention and treatment.